I assume you're asking to solve for the n-th term in the sequence, [tex]a_n[/tex].
From the given recursive rule,
[tex]a_n = a_{n-1} + 2 \implies a_{n-1} = a_{n-2} + 2[/tex]
and by substitution,
[tex]\implies a_n = a_{n-2} + 2\times2[/tex]
Similarly,
[tex]a_n = a_{n-1} + 2 \implies a_{n-2} = a_{n-3} + 2[/tex]
[tex]\implies a_n = a_{n-3} + 3\times2[/tex]
The pattern continues, so that we can write the n-th term in terms of the 1st one:
[tex]a_n = a_1 + (n-1)\times2 \implies a_n = 10 + 2(n-1) = \boxed{2n+8}[/tex]
So the first few terms of the sequence are
{10, 12, 14, 16, 18, 20, …}